2014
DOI: 10.1186/s12862-014-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hypoxia-inducible factor alpha polyploidization reveals adaptation to Tibetan plateau in the evolution of schizothoracine fish

Abstract: BackgroundHypoxia-inducible factor (HIF) is a master regulator that mediates major changes in gene expression under hypoxic conditions. Though HIF family has been identified in many organisms, little is known about this family in schizothoracine fish.ResultsDuplicated hif-α (hif-1αA, hif-1αB, hif-2αA, and hif-2αB) genes were identified in schizothoracine fish. All the deduced HIF-α proteins contain the main domains (bHLH-PAS, ODDD, and TAD), also found in humans. Evidence suggests a Cyprinidae-specific deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 72 publications
6
52
1
Order By: Relevance
“…Hif-1αB and hif-2αA genes of T. dalaica were also found to experience positive selection, which may have led to changes in function to cope with the highaltitude life. On the one hand, the results validated the conclusion that the specialized and highly specialized schizothoracine fish HIF-1αB have experienced significantly selective pressure (Guan et al, 2014). On the other hand, hif-2αA genes experienced positive selection in T. dalaica indicated that fish and mammals may have developed similar mechanisms to adapt to the extreme environment of the Tibetan Plateau.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Hif-1αB and hif-2αA genes of T. dalaica were also found to experience positive selection, which may have led to changes in function to cope with the highaltitude life. On the one hand, the results validated the conclusion that the specialized and highly specialized schizothoracine fish HIF-1αB have experienced significantly selective pressure (Guan et al, 2014). On the other hand, hif-2αA genes experienced positive selection in T. dalaica indicated that fish and mammals may have developed similar mechanisms to adapt to the extreme environment of the Tibetan Plateau.…”
Section: Discussionsupporting
confidence: 74%
“…Some candidate genes involved in the HIF-1 signaling pathway have been shown to exhibit signatures of positive selection in Tibetans, yak, ground tit, Tibetan mastiff, and schizothoracine fish living in the Tibetan Plateau (Beall et al, 2010;Bigham et al, 2010;Storz, 2010;Qiu et al, 2012;Qu et al, 2013;Guan et al, 2014;Li et al, 2014). EPAS1 (HIF-2α), EGLN1, and PPARA in Tibetans, ADAM17 and Arg2 in yak, SRF, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible that positive selection on the mitochondrial genomes of these fish reflects adaptive evolution to the hypoxic environment at high altitudes. Interestingly, Guan et al (2014) also reported positive selection of hypoxia-inducible factor alpha B (HIF-αB), which is an important regulator of gene expression under hypoxic conditions, in the morphologically specialized Schizothoracinae clade. Branch1 is the common ancestor of the morphologically specialized clade.…”
Section: ω=1 Pro=0%mentioning
confidence: 99%